ANALYSIS OF CHROMIUM (Cr) AND IRON (Fe) IN SEVERAL WELL WATER IN KAMPUNG BATIK KAUMAN SURAKARTA USING ATOMIC ABSORPTION SPECTROPHOTOMETRY (AAS) - Saidah, Saidah; Gripaldi, Fakhry; Gasim Soka, Burhanudin; Hasan, Rahmawaty; Wijaya, Heri (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
Water is a fundamental necessity for life, as all living organisms depend on it for survival. Industrial wastewater such as that generated from leather, paper, textile, and batik industries may contain chromium and iron used as dyes, which can pose serious health risks if they enter the human body. The experiment was aimed to find out whether there were chromium and iron in well water at Batik Village Kauman Surakarta, and to know whether the contents of chromium and iron do not exceed the maximum limit. The experiment was done by Atomic Adsorption Spectrophotometry, because this method could analyze the elements precisely and accurately. The sample was acidified with HNO3 concentrated before analyzed & then put into beaker glass & evaporated, & removed into volumetric flask & added with bi-distill ed water up to the mark. The result of the experiment showed that all samples of well water did not contain chromium, but they contained iron. The iron content in sample A =(0.1821±0.0303) ppm; sample B = (0.1251 ± 0.0108) ppm, sample C = (0.6364 ±0.2394) ppm. The contents of iron in the three well water samples fulfill the requirements of Indonesian National Standard No. 01-0220-1987.